Management of accidental exposure to Ebola virus in the biosafety level 4 laboratory, Hamburg, Germany - Günther, Stephan; Feldmann, Heinz; Geisbert, Thomas W; Hensley, Lisa E; Rollin, Pierre E; Nichol, Stuart T; Ströher, Ute; Artsob, Harvey; Peters, Clarence J; Ksiazek, Thomas G; Becker, Stephan; ter Meulen, Jan; et al. (The Journal of infectious diseases, 2011)
A needlestick injury occurred during an animal experiment in the biosafety level 4 laboratory in Hamburg, Germany, in March 2009. The syringe contained Zaire ebolavirus (ZEBOV) mixed with Freund's adjuvant. Neither an approved treatment nor a postexposure prophylaxis (PEP) exists for Ebola hemorrhagic fever. Following a risk-benefit assessment, it was recommended the exposed person take an experimental vaccine that had shown PEP efficacy in ZEBOV-infected nonhuman primates (NHPs) [12]. The vaccine, which had not been used previously in humans, was a live-attenuated recombinant vesicular stomatitis virus (recVSV) expressing the glycoprotein of ZEBOV. A single dose of 5 × 10(7) plaque-forming units was injected 48 hours after the accident. The vaccinee developed fever 12 hours later and recVSV viremia was detectable by polymerase chain reaction (PCR) for 2 days. Otherwise, the person remained healthy, and ZEBOV RNA, except for the glycoprotein gene expressed in the vaccine, was never detected in serum and peripheral blood mononuclear cells during the 3-week observation period.